AN ANALYSIS OF STUDENTS’ ABILITY IN WRITING RECOUNT TEXT AT THE TENTH GRADE OF SMK TIGAMA PEKANBARU - Ayu Yunita Putri Br. Barus; Erni Erni; Jismulatif Jismulatif (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research aims to analyze the students’ ability in writing recount text at the tenth grade students of SMK Tigama Pekanbaru. This research was used descriptive research. The population of this research were the tenth grade students of SMK Tigama Pekanbaru. The sample of this research was X Cullinary Art, consist of 33 students who have been the participants for this research. In collecting the data, the researcher used writing test. The writing test were analyzed by ESL Profile Composition by Jacob (1981). There are five aspects have been analyzed: content, organization, vocabulary, language use and mechanic. The findings of this research revealed that students got good to average in content, organization, vocabulary and mechanic aspects and excellent to very good in language use aspect. As the result of this research, it showed that the majority of the students perform well in the content, organization, vocabulary, language use and mechanic aspects of writing recount text.Keywords: Analysis, Ability, Writing, Recount Text